The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/ijerph15112468
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Family Violence and Self-Control in Adolescence: A Multi-Level Meta-Analysis

Abstract: Theoretical studies propose an association between family violence and low self-control in adolescence; however, empirical findings of this association are inconclusive. The aim of the present research was to systematically summarize available findings on the relation between family violence and self-control across adolescence. We included 28 studies with 143 effect sizes, representing more than 25,000 participants of eight countries from early to late adolescence. Applying a three-level meta-analysis, taking … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 111 publications
2
24
0
1
Order By: Relevance
“…Such imbalances in the development of self-control underline the need to examine the role of different types of self-control in the “school discipline–self-control” association. Therefore, in this study, we not only operationalize self-control as general self-control, as many other meta-analyses about self-control did (De Ridder et al, 2012; Li et al, 2019; Willems et al, 2019; Willems, Li, et al, 2018), but we also differentiate between different types of self-control and examine whether the type of self-control moderates the association between school discipline and self-control.…”
Section: Conceptualization Of School Disciplinementioning
confidence: 99%
See 1 more Smart Citation
“…Such imbalances in the development of self-control underline the need to examine the role of different types of self-control in the “school discipline–self-control” association. Therefore, in this study, we not only operationalize self-control as general self-control, as many other meta-analyses about self-control did (De Ridder et al, 2012; Li et al, 2019; Willems et al, 2019; Willems, Li, et al, 2018), but we also differentiate between different types of self-control and examine whether the type of self-control moderates the association between school discipline and self-control.…”
Section: Conceptualization Of School Disciplinementioning
confidence: 99%
“…Although self-control has biological underpinnings, existing studies have also suggested that self-control can be substantially shaped by the environment (Willems, Dolan, et al, 2018; Willems et al, 2019). Many studies have considered family as the primary context that nurtures child and adolescent self-control (Davis et al, 2017; Karreman et al, 2006; Li et al, 2019; Pallini et al, 2018; Willems, Li, et al, 2018). Besides family, the school is another important developmental context for children when they start formal education (Bronfenbrenner, 1979; Downer et al, 2010).…”
mentioning
confidence: 99%
“…Yet, not all individuals develop the same levels of selfcontrol, which begs the question: 'where do these individual differences come from?'. While the effects of the environment on such individual differences are well documented (Bridgett et al, 2015;Pallini et al, 2018;Willems et al, 2018b), the research on genetic influences on selfcontrol is more nascent. The aim of this study is therefore to perform a meta-analysis to provide a quantitative overview of the heritability of self-control.…”
Section: Self-control Twin Heritability Meta-analysis Geneticsmentioning
confidence: 99%
“…In addition, these parental practices have been associated with serious behavioral and psychosocial adjustment problems in adolescents, variables that are closely linked to violence in couple relationships [25]. By contrast, the behaviors and attitudes that represent healthy family functioning (cohesion, support, and positive communication) are related to good psychological and emotional development in the children [26,27].…”
Section: Introductionmentioning
confidence: 99%